Oblikovanje prilagodljivega obdelovalnega sistema z genetskimi algoritmi - Ficko, Mirko (Strojniški vestnik, 2005)
It is well-known that with a proper layout of devices in a flexible manufacturing system it is possible to reduce the variable transport costs and, consequently, the total manufacturing costs, and thus secure a competitive advantage. So far, a variety of methods of layout have been introduced, but the problem has not been satisfactorily solved. This paper describes a method of placing machines and devices in a FMS using a genetic algorithm method. The line layout of the units of the FMS system is assumed. With the proposed method it is possible to ensure optimum layout with respect to the set target function including variable transport costs.
Keywords: sistemi obdelovalni prilagodljivi; algoritmi genetski; prenos notranji; razporeditve strojev; obdelovalni sistemi; genetski algoritmi; postrojenje